PENGGUNAAN MULTIMEDIA INTERAKTIF BERORIENTASI GUIDED EXPERIMENT DENGAN MODEL Project Based Learning (PjBL) UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV SEKOLAH DASAR - Indah Setyaning Usri Yusro; Vuri Putri Yonatin; Heri Maria Zulfiati; Daimul Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The pupose of this study was to increase students attention and learning outcomes on social studies learning content through the project based learning approach in class IV at SDN Guntur temanggung. The research subjects were student of class IV with 10 students consist of male 6 students, female 4 students. Based on the results of the study, it shows that student learning outcomes increase with increasing student attention and interes in social studies learning materials through a project-based learning approach. This can be sen from the student learning outcomes in the form of learning completeness. The conclusion of this study shows that the Project Based Learning model can increase interest and learning outcomes of fourth grade students of SDN Guntur Temanggung. The purpose of this research is to improve science learning outcomes with the help of project-based learning models.